Structure Of Polychaeta Community In Banyuasin Mangrove Coast Waters, South Sumatera - Yosafat Tawanggian; Zazili Hanafiah; Dwi Putro Priadi (Program Pascasarjana Universitas Sriwijaya, 2022)
This study aims to determine the Structure of Polychaeta Community, and how the physical and chemical conditions and describe water conditions based on aquatic biota. The research time took place in April – October 2020. The determination of the sampling location was carried out using the Purposive Sampling method, which is based on differences in environmental baseline around. Identification of polychaeta samples was carried out at the Animal Ecology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Sriwijaya University, Indralaya. The results obtained 22 polychaeta genera consisting of 22 classes namely Sternaspidae, Arenicolidae, Ctenodrilidae, Parergodrilidae, Magelgnidae, Heterospionidae, Capitellidae, Scalibregmidae, Ophellidae, Pontodoridae, Pisionidae, Hesionidae, Eunicidae, Flabelligeridae, Fauveliopsidae, Neriophilidae, Culiridae Cossuridae, Alciopidae, and Nereididae. The species diversity index belongs to the medium category, which ranges from 1.8 to 2.81. The dominance index of polychaeta in the coastal waters of the Banyuasin mangrove is relatively small or no species dominates because all stations have an average dominance index value below 0.5. While the physico-chemical factors of the waters in this river are classified as stable.